2020
DOI: 10.1016/j.tibs.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Netrin Synergizes Signaling and Adhesion through DCC

Abstract: Netrin is a prototypical axon guidance cue. Structural studies have revealed how netrin interacts with the deleted in colorectal cancer (DCC) receptor, other receptors, and co-factors for signaling. Recently, genetic studies suggested that netrin is involved in neuronal haptotaxis, which requires a reversible adhesion process. Structural data indicate that netrin can also mediate trans-adhesion between apposing cells decorated with its receptors on the condition that the auxiliary guidance cue draxin is presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…4a) and thereby enhancing the weak D1mediated self-association. We note with interest that recent structural studies of deleted in colorectal cancer (DCC), a netrin receptor, important for axon navigation, suggests the associations of DCC with both its extracellular and intracellular binding partners play roles in mediating the receptor clustering [52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…4a) and thereby enhancing the weak D1mediated self-association. We note with interest that recent structural studies of deleted in colorectal cancer (DCC), a netrin receptor, important for axon navigation, suggests the associations of DCC with both its extracellular and intracellular binding partners play roles in mediating the receptor clustering [52][53][54][55] .…”
Section: Discussionmentioning
confidence: 99%
“…We found that tumor mutations of members of the Netrin family showed a unique distribution pattern for cancer type, protein structure, and ethnic group. It is worth noting that a significant number of missense or truncating mutations have been found in the Laminin N-terminal and EGF domains that interact with related receptors 55,56 and the regulatory localization of the NTR domain 57,58 . Thus, the molecular mechanisms related to receptor affinity and spatial localization should be thoroughly investigated at the level of structural biology and biochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that draxin controls axon guidance through netrin-1 receptors, Deleted in colorectal cancer (Dcc) and Neogenin (Neo1) ( Ahmed et al, 2011 ; Shinmyo et al, 2015 ). Draxin has also been shown to modulate netrin-1-mediated axon guidance and fasciculation ( Gao et al, 2015 ; Liu et al, 2018 ; Meijers et al, 2020 ). In this review, we highlight possible roles of draxin/netrin-1 signaling in the development of spinal commissural axons, corpus callosum, and thalamocortical axons.…”
Section: Introductionmentioning
confidence: 99%